Système métropolitain et logique de projet : une approche de la question urbaine en géographie et aménagement - Anne-Peggy Hellequin; Nathalie Lemarchand; Didier Paris (Territoire en Mouvement)
This article can be seen as an attempt to identify the contours of urban studies in such a way that the journal Territoire en Mouvement could precise its own working path. A first general observation shows that the scientific thought on the urban phenomenon has often gone along with the political discourses. In a spatial perspective, urban territories are often described as complex systems where economic and social components overlap. In this way, the metropolization process can be seen as a territorialized developmental model, in which local actors are forced to act in synergy. Where it emerges, the urban project thus becomes a paradigm for the discussion on its design, its places and on the social project it bears. Experimentations in the Nord - Pas de Calais region north of France, most notably within the metropolitan region of Lille, provides god insights in this debate, as shown by the fact that the notion of urban renewal was first put forward in the region.